Sliding signal processing in telecommunication networks based on two-dimensional discrete Fourier transform - Ponomarev Vladimir; Ponomareva Olga; Ponomarev Alexey; Smirnova Natalya (ITM Web of Conferences, 2019)
A method of vertical sliding processing of two-dimensional discrete signals in the spatial frequency domain is proposed — a method of fast vertically sliding two-dimensional discrete Fourier transform. The mathematical representation of the two-dimensional discrete Fourier transform in algebraic and matrix form is considered. An effective method of vertically sliding two-dimensional discrete Fourier transform is proposed. The algorithm developed in the framework of the proposed method allows calculating the coefficients (bins) of this transformation in real time.